2013
DOI: 10.1016/j.jpeds.2012.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Acute Necrotizing Pancreatitis in Children

Abstract: Objective Necrotizing pancreatitis is very rare in children. In this case series, we describe the etiologic factors, course, and outcome of acute necrotizing pancreatitis in children. Study Design We performed a retrospective study of children with necrotizing pancreatitis diagnosed over the last 21 years at Yale New Haven Children’s Hospital. Computed tomography (CT) scan criteria were used to diagnose necrotizing pancreatitis and to assess severity index. Charts were reviewed to collect demographic data, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 20 publications
2
32
2
4
Order By: Relevance
“…According to the literature [19], necrotizing pancreatitis occurs in less than 1% of children with AP. Among the ve large sample pediatric cases reported in the United States [20], only 3 of 1014 children with AP had pancreatic necrosis, which was signi cantly less severe than that of adults.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature [19], necrotizing pancreatitis occurs in less than 1% of children with AP. Among the ve large sample pediatric cases reported in the United States [20], only 3 of 1014 children with AP had pancreatic necrosis, which was signi cantly less severe than that of adults.…”
Section: Discussionmentioning
confidence: 99%
“…1 El dolor abdominal suele ser de inicio brusco, continuo y ocasiona una posición antiálgica. En casos graves, puede aparecer una coloración azulada periumbilical (signo de Cullen) y en los flancos (signo de Grey Turner) o desarrollarse derrame pleural, ascitis, ictericia e, incluso, un síndrome de respuesta inflamatoria sistémica con fallo multiorgánico y elevada morbimortalidad (en torno a 17%).…”
Section: Comentariosunclassified
“…1,6 La ecografía abdominal es la primera prueba de imagen por realizar, y se reserva la TAC para los casos de evolución desfavorable. La gravedad y el riesgo de complicaciones asociadas puede valorarse mediante TAC según el puntaje de Balthazar, que otorga una puntuación en función del grado de inflamación y de necrosis (de menor grado, A, a mayor, E).…”
Section: Comentariosunclassified
See 1 more Smart Citation
“…Age is one of the indices used to grade the severity of AP in clinical scoring systems such as the Ranson criteria [5], the Bedside Index for Severity in Acute Pancreatitis [6] and the Acute Physiology and Chronic Health Evaluation II [7]. In addition, in recent years, some researchers have studied the relationship between age and AP and found that different age stages have certain unique characteristics of AP, such as incidence, etiology, mortality [8][9][10], and there are also studies analyzing AP in certain age stage [11,12]. In clinical practice, we have found that the progression and prognosis of ANP are not completely the same in patients of different ages.…”
Section: Introductionmentioning
confidence: 99%